Russian Version of the Handelman's Adolescent Apathy Inventory - Zolotareva A.A (Moscow State University of Psychology and Education, 2019)
The present study aimed at Russian-language adaptation and validation of the Handelman's Adolescent Apathy Inventory (AAI).The study group consists of 346 students, who are enrolled into Omsk State Technical University (OmSTU).Results from exploratory and confirmatory factor analyses confirmed the measure's one-dimensional structure.Moreover, correlation analyses provided evidence for the inventory's convergent and divergent validity: adolescent apathy showed positive correlations with alienation from study (OSA-S) and amotivation (AMS-C) and negative correlations with intrinsic motivation for knowledge, intrinsic motivation toward accomplishments, intrinsic motivation for stimulation, intrinsic motivation for self-respect, identified regulation, introjected regulation, extrinsic regulation (AMS-C), vigor and dedication (UWES-S).In addition, inventory showed good reliability (α-Cronbach = 0,76) and temporal stability over one-month period (mean test-retest correlation = 0,71).The present findings provide adequate support for the reliability and validity of the Russian version Adolescent Apathy Inventory.